Teach them all to read catching the kids who fall through the cracks - McEwan-Adkins, Elaine K. 1941- (Corwin Press, 2002)
"This insightful and practical book offers teachers at all levels the understanding and motivation they need to teach children to read-especially those students who need help the most."